POTENSI PERTANIAN SEBAGAI PENGGERAK UTAMA DI MASYARAKAT DESA MATARU SELATAN KECAMATAN MATARU KABUPATEN ALOR - Penina Maruli; Marsia Alomau; Marthalin Lanmai; Priska Lakatina; Petrus Mau Tellu Dony (Adiba Aisha Amira, 2026)
The purpose of this study is to describe the potential of the agricultural sector as the main driver of economic development in the South Mataru Village community, as well as to examine its role in improving community welfare. The research method uses a qualitative descriptive approach through observation and interviews with village officials, as well as a literature review. The results of the study indicate that agriculture is a dominant sector that has a large contribution to household income, local food security, and the potential for developing superior village products. The main challenges found include limited infrastructure, access to technology, and marketing of agricultural products. Research recommendations include increasing farmer capacity, commodity diversification, and supporting village-based government programs.